Systematic Literature Review Implementasi Kurikulum Pesantren dalam Peningkatan Mutu Santri (Pascasarjana IAIN Kudus, 2024)
A Systematic Literature Review Implementation of Pesantren Curriculumin Santri Quality Improvement. In both formal and non-formal educational contexts, the curriculum is a fundamental element in the pursuit of academic objectives. The curriculum is implemented in the learning process at Pesantren, as it is in schools. The objective of this study was to conduct a review of the existing research on the impact of curricular implementation on student quality. The objective of this study was to conduct a comprehensive review of the existing literature on the impact of curriculum implementation on student quality. This study employed a literature review in accordance with the PRISMA (Preferred Reporting Items for Systematic Review and Meta-analyses) guidelines. The data was obtained by collating a range of articles that addressed similar research questions to those explored in this study. The articles employed in this study were 22 national journal articles accredited between 2018 and 2022, numbered from Sinta 1 to Sinta 3. The findings of this study suggest that the quality of students can be enhanced through the implementation of the curriculum in Pesantren. The primary objective of Pesantren education, as evidenced by the literature review, is to produce graduates who are able to harmoniously integrate IPTEK (Science and Technology) and IMTAQ (Faith and Taqwa) in their lives.Kurikulum menjadi hal yang fundamental dalam mencapai tujuan pendidikan, baik dalam ruang lingkup pendidikan formal maupun non-formal. Sama halnya dengan sekolah, pesantren juga menerapkan kurikulum dalam proses pembelajarannya. Tujuan penelitian ini adalah untuk melakukan kajian literatur sistematis terkait dengan implementasi kurikulum dalam peningkatan mutu santri. Metode penilitian yang digunakan adalah metode systematic literature review dengan model PRISMA (Preferred Reporting Items for Systematic Review and Meta-analyses) mengumpulkan berbagai artikel yang memiliki penelitian serupa pada penelitian ini. Artikel yang digunakan pada penelitian ini sebanyak 22 artikel jurnal nasional yang terakreditasi sinta 1 sampai sinta 3 dan diambil dari tahun 2018 sampai tahun 2022. Hasil penelitian ini menunjukkan bahwa implementasi kurikulum dalam pendidikan pesantren mampu meningkatkan mutu santri. Hal ini selaras dengan kajian literatur yang dilakukan bahwa tujuan akhir dari pendidikan pesantren adalah menghasilkan generasi lulusan yang mampu menyeimbangkan IPTEK (Ilmu Pengetahuan dan Teknologi) dan IMTAQ (Iman dan Taqwa) dalam kehidupan.